Semantic Web technologies for digital libraries - Ragab Hassanin (Cybrarians Journal, 2007)
Whenever a new technology appears in the field of information technology, library workers seek to benefit from its applications in their field. A new technology has appeared in search engines and information retrieval systems, which is called the Semantic Web, which is a new revolution in the field of search engines and the development of tools for retrieving information from the World Wide Web. One of its important applications is building digital libraries using the capabilities of the Semantic Web, and this is what we will learn about in these lines.